Case report:Multiple abscesses caused by Porphyromonas gingivalis diagnosed by metagenomic next-generation sequencing - Zhang, Yichen; Zhu, Youfeng; Wan, Huijuan (Frontiers in Medicine, 2023)
Background Extraoral infection by Porphyromonas gingivalis (P. gingivalis) is extremely rare and challenging to diagnose because the fastidious pathogen is difficult to culture by traditional methods. We report the first case of a patient with multiple abscesses in muscles and the brain with dura empyema due to P. gingivalis, which was diagnosed by metagenomic next-generation sequencing (mNGS). Case presentation A 65-year-old male patient was admitted to our hospital for multiple lumps in his body. Brain magnetic resonance imaging (MRI) and lower-limb computed tomography (CT) revealed multiple abscesses in the brain and muscles. A diagnosis of P. gingivalis infection was made based on mNGS tests of blood, cerebrospinal fluid (CSF), and pus samples, as the traditional bacterial culture of these samples showed negative results. Target antibiotic therapy with meropenem and metronidazole was administered, and CT-guided percutaneous catheter drainage of abscesses in both thighs was performed. The size of muscle abscesses reduced significantly and neurological function improved. The patient was followed up for 4 months. No abscesses re-appeared, and the remaining abscesses in his backside and both legs were completely absorbed. He can speak fluently and walk around freely without any neurological deficits. Conclusion Metagenomic next-generation sequencing is helpful for early diagnosis and subsequent treatment of P. gingivalis-associated multiple abscesses.